Khat and synthetic cathinones: a review - Valente, Maria João (2021)
For centuries, 'khat sessions' have played a key role in the social and cultural traditions among several communities around Saudi Arabia and most East African countries. The identification of cathinone as the main psychoactive compound of khat leaves, exhibiting amphetamine-like pharmacological properties, resulted in the synthesis of several derivatives structurally similar to this so-called natural amphetamine. Synthetic cathinones were primarily developed for therapeutic purposes, but promptly started being misused and extensively abused for their euphoric effects. In the mid-2000's, synthetic cathinones emerged in the recreational drug markets as legal alternatives ('legal highs') to amphetamine, 'ecstasy', or cocaine. Currently, they are sold as 'bath salts' or 'plant food', under ambiguous labels lacking information about their true contents. Cathinone derivatives are conveniently available online or at 'smartshops' and are much more affordable than the traditional illicit drugs. Despite the scarcity of scientific data on these 'legal highs', synthetic cathinones use became an increasingly popular practice worldwide. Additionally, criminalization of these derivatives is often useless since for each specific substance that gets legally controlled, one or more structurally modified analogs are introduced into the legal market. Chemically, these substances are structurally related to amphetamine. For this reason, cathinone derivatives share with this drug both central nervous system stimulating and sympathomimetic features. Reports of intoxication and deaths related to the use of 'bath salts' have been frequently described over the last years, and several attempts to apply a legislative control on synthetic cathinones have been made. However, further research on their pharmacological and toxicological properties is fully required in order to access the actual potential harm of synthetic cathinones to general public health. The present work provides a review on khat and synthetic cathinones, concerning their historical background, prevalence, patterns of use, legal status, chemistry, pharmacokinetics, pharmacodynamics, and their physiological and toxicological effects on animals and humans.